Research on deterministic network technology and its development trends - Gao Fangfang; Chen Yan; Liu Meihui; Shen Bin; Xu Qichen (Dianzi Jishu Yingyong)
With the continuous emergence of emerging applications, more and more businesses require reliable transmission with low latency and low jitter. Especially in industrial scenarios, the number of access network devices has surged, and the network is developing towards large-scale and complex directions. How to ensure the deterministic delivery of key data streams has become a research focus. Deterministic network technology has received widespread attention due to its characteristics such as low latency, low jitter, low packet loss rate, deterministic bandwidth, and highly reliable transmission, and has good application prospects in fields such as automotive, energy, and industrial automation. The key technologies of deterministic networks are elaborated, the deterministic network fusion deployment solutions in two different scenarios are introduced, and finally the challenges faced by deterministic network technologies in practical application are analyzed.